A million answers to twenty questions: Choosing by checklist - Michael Mandler; Paola Manzini; Marco Mariotti (Queen Mary University of London, Department of Economics, 2008)
Many decision models in marketing science and psychology assume that a consumer chooses by proceeding sequentially through a checklist of desirable properties. These models are contrasted to the utility maximization model of rationality in economics. We show on the contrary that the two approaches are nearly equivalent. Moreover, the length of the shortest checklist as a proportion of the number of an agent's indifference classes shrinks to 0 (at an exponential rate) as the number of indifference classes increases. Checklists therefore provide a rapid procedural basis for utility maximization.
Keywords: D01; 330; Bounded rationality; Procedural rationality; Utility maximization; Choice behavior; Beschr\~AƒÂnkte Rationalit\~AƒÂt; Eigeninteresse; Entscheidungstheorie; Theorie